(3HQgGf GdbQBf deG ajg ef GdMLI hGdHjGfs - (3GdcQeGfj , HQgGf GdOjf CHh GdbGSe eMehO Hf MeRI Hf fUQ GdcQeGfj GdebQj GdTGaYj, JGL GdbQGA,J (B505 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg CNHQfG GdTjN GdaGVd Yaja GdOjf TQa GdbQGA aQjO GdYUQ CHh eci eMeO Hf MGeO GdCUagGfi CNHQfG GdEeGe GdCLd GdcHjQ aNQ GdOjf LeGd GdESdGe s
(3BNQgG (B:s
(3bGd GdTjN GdEeGe ced cJGH HQgGf GdbQBf HaVd Gddg GdefGf hbO ChQOJ ajg LejY eG Ohf GdSda ef GdeJTGHg ai cJHge hGVaJ Edjg eG SfM Hg GdNGWQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B168 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B161s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B241s
Keywords: (3GdbQGAGJ hGdJLhjOs